Вплив міжнародних фінансових інституцій на економічний розвиток країн - Коляда, Тетяна Анатоліївна; Олексієнко, Тетяна Миколаївна (Інфраструктура ринку, 2018)
У статті досліджено роль та значення міжнародних фінансових інституцій як вагомого інструмента зовнішніх фінансових ресурсів. Узагальнено наукові підходи до використання міжнародної фінансової допомоги для економічного розвитку країн. Зроблено висновок про необхідність зваженого підходу до оцінювання співробітництва з міжнародними фінансовими організаціями та з’ясування переваг і недоліків залучення до національних економік фінансових ресурсів цих інституцій.

The subjects of the study are theoretical and practical questions which were related to the role of international financial institutions (IFI’s) in the financing of the public development of the country. The article purpose is the opening to the reveal inﬂuence of the international financial and credit institutions in the financing of the public and economy development of the country. The paper used the set of general scientific and specific methods and approaches, such as dialectic, systems, the method of scientific abstraction, comparative and factor analysis, logical approach. The article investigates theoretical approaches to the economic nature of the financial resources of international institutions and their role in the economic development of the country. In the article the basic scientific approaches to understanding the effects of aid ﬂows to the poorest developing countries. Cooperation with leading MFIs in countries with economies in transition, in the initial phase transformations, played an important role in solving strategic tasks such as restructuring of economic systems, systems of property and material production, the introduction of effective models of industrial and technological policy and so on. However, it should be noted that although loans MFIs and is one of the most common tools accumulation of resources to national economies, promoting inclusion recipient countries to international financial and capital markets but requires a balanced approach to the cooperation with international financial institutions and the strengths and weaknesses of national economies to attract loan capital of these institutions. The conclusion about deliberate approach to the estimation of the collaboration with international financial organizations and to the elucidation of advantages and shortcomings of the attraction of the capital of those institutions to the national economies is indicated. The additional financial resources as the part of the external official aid allow introducing the latest technologies and financing mechanisms of IFO, which improving the best management of the financial resources and increasing the effectiveness of their using.
Keywords: міжнародні фінансові інститути; економічний розвиток; фінансова допомога; фінансові ресурси; international financial institutions; economic development; financial aid; financial resources